2017
DOI: 10.5530/jcdr.2017.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Echocardiographic Parameters to Outcome of Patients with Severe Sepsis and Septic Shock

Abstract: Background: Myocardial dysfunction is one of the most important features of sepsis. The presence of cardiac dysfunction in sepsis has been associated with high mortality rate in septic patients. Material & Methods: This was prospective, observational cohort (patient with severe sepsis and septic shock) study conducted over period of one year in medical intensive care unit. Patients with an initial diagnosis of severe sepsis or septic shock were enrolled. Aims & Objectives:To study demographic profile, APACHE-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In contrast to our study, Patil et al found that the mean LVEF was 35.70% and more than 70% of septic patients had SD, and the mortality rate was high in patients with impaired EF (< 50%) more than patients with normal EF (15% vs. 34%, respectively). 11 Another study by Vieillard-Baron and colleagues on 67 patients free from previous cardiac disease and survived for > 48 h stated that global LV hypokinesia (EF < 45%) was found in 60% of the septic patients. 12 The left atrium (LA) size is used as a diagnostic criterion for DD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, Patil et al found that the mean LVEF was 35.70% and more than 70% of septic patients had SD, and the mortality rate was high in patients with impaired EF (< 50%) more than patients with normal EF (15% vs. 34%, respectively). 11 Another study by Vieillard-Baron and colleagues on 67 patients free from previous cardiac disease and survived for > 48 h stated that global LV hypokinesia (EF < 45%) was found in 60% of the septic patients. 12 The left atrium (LA) size is used as a diagnostic criterion for DD.…”
Section: Discussionmentioning
confidence: 99%